2012
DOI: 10.3233/jbr-2012-030
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation in vitro of highbush blueberry (Vaccinium corymbosum L.)

Abstract: Murashige and Skoog medium (MS) and modified Anderson's Rhododendron medium (mAN) were compared for in vitro shoot multiplication of three highbush blueberries 'Berkeley', 'Bluecrop' and 'Goldtraube'. All media contained 0.5 mg l −1 zeatin applied either alone or combined with 0.1, 1 and 5 mg l −1 IBA. In vitro rooting was induced using mAN medium supplemented with 0.8 mg l −1 IBA and 4 g l −1 activated charcoal. The results obtained showed that mAN medium is more suitable for in vitro multiplication of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
4
24
1
1
Order By: Relevance
“…The dependence of plant tissue on exogenous growth regulators to induce adventitious shoots was well documented in blueberry (Sharma & Thorpe 1989, Gajdošová et al 2006, Meiners et al 2007, Liu et al 2010. Many of them were reported that the combination of cytokinins and auxins to induce plant regeneration (Rowland & Ogden 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of plant tissue on exogenous growth regulators to induce adventitious shoots was well documented in blueberry (Sharma & Thorpe 1989, Gajdošová et al 2006, Meiners et al 2007, Liu et al 2010. Many of them were reported that the combination of cytokinins and auxins to induce plant regeneration (Rowland & Ogden 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These limitations can be overcome by the utilization of in vitro culture techniques, and the most effective propagation system for blueberries is micropropagation due to the rapid and continuous production of a large number of plants. Over the last three decades, in vitro culture propagation on the various basal medium using axillary bud proliferation and adventitious shoot regeneration with different explants has been achieved with varying success (Gajdošová et al 2006, Li et al 2006. The culture of blueberries in North America has been more than one hundred years up to now where is the origin place for blueberry.…”
Section: Preparation Of Explantsmentioning
confidence: 99%
“…Artificial/synthetic cytokinins zeatin, thidiazuron (TDZ), and 2-isopentenyladenine (2iP), have been used to promote in vitro shoot formation from internodal cuttings, with multiple reports that zeatin is the most effective at shoot regeneration [8,9]. Zeatin is still widely used in High Chilling (HC) cultures [8,10], where the media concentration range varies among publications between 0.5 and 4 mg/L [8,9,11,12]. The optimal amount is not only genotype-specific, it also depends on the desired application, as cytokinins affect meristem proliferation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Light can also be considered a plant growth regulator as different light wavelengths, intensity and amounts can initiate intracellular signaling cascades for example causing conformational changes in the backbone of cellular receptors called phytochromes, which can then transition to their biologically active form [14,15]. and 4 mg/L [8,9,11,12]. The optimal amount is not only genotype-specific, it also depends on the desired application, as cytokinins affect meristem proliferation [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, Nezami-Alanagh et al (2017) fund that gluconate − had an adverse effect on in vitro pistachio plant growth. In high-bush blueberry (Vaccinium corymbosum L.), the use of MS medium induced STN, especially when 0.5 mg/l zeatin was used with higher concentrations (> 1 mg/l) of IBA, but when this was replaced by Anderson's rhododendron medium (Anderson 1984), STN was eliminated (Ružić et al 2012). Anderson's rhododendron medium, relative to MS medium, contains about one-quarter the concentration of K + , NH + 4 and NO − 3 (Suppl.…”
Section: Choice Of Basal Mediummentioning
confidence: 99%